Intensity modulated radiotherapy with carbon ion radiotherapy boost for acinic cell carcinoma of the salivary glands - Schmid, Maximilian P.; Held, Thomas; Uzun-Lang, Kristin; Herfarth, Klaus; Hörner-Rieber, Juliane; Harrabi, Semi B.; Moratin, Julius; Freudlsperger, Christian; Plath, Karim; Debus, Jürgen; Adeberg, Sebastian (Cancers, 2021)
Aim: to report clinical outcome in patients with acinic cell carcinoma of the salivary glands treated with intensity-modulated radiotherapy (IMRT) and carbon ion radiotherapy (CIRT) boost. Materials and Methods: all patients with acinic cell carcinoma of the salivary glands treated at the Heidelberg Ion-Beam Therapy Center were considered for this retrospective analysis. All patients received a CIRT boost with 18–24 Gy radiobiologic effectiveness (RBE)-weighted dose in 3 Gy RBE-weighted dose per fraction followed by IMRT, with 50–54 Gy in 2 Gy per fraction. Disease outcome was evaluated for local (LR), nodal (NR), distant recurrence (DR), and disease-free (DFS) and overall survival (OS). Morbidity was scored based on Common Terminology Criteria for Adverse Events (CTCAE) version 5. Descriptive statistics and the Kaplan-Meier method were used for analysis. Results: fifteen patients were available for analysis. Median follow-up after radiotherapy was 43 months. Six patients were treated for primary disease and nine for recurrent disease. Eight patients were treated with radiotherapy for macroscopic disease. Disease recurrence was observed in four patients: 1 LR, 2 NR, and 2 DR; 5-year local control, DFS, and OS were 80%, 52%, and 80%, respectively. No radiotherapy-related G3-5 morbidity was observed. Conclusion: In acinic cell carcinoma, IMRT with carbon ion radiotherapy boost leads to excellent results after R1-resection and is a promising treatment modality for definitive treatment in inoperable patients.
Gesehen am 04.02.2021